University as a Living Learning Lab for Sustainable Futures - Rukspollmuang, Chanita; Mongkhonvanit, Pornchai; Phitthayanon, Chanida; Silalai, Nattiga; Nubsang, Haritchaya (Universitas Diponegoro, 2022)
“Leading University Creating Innovation for Sustainable Future”, the vision of Siam University, reflects our commitment to ensure that all learners acquire necessary mindset, skills, values, and knowledge to become co-creators of a more sustainable futures. The vision has been implemented in a whole institution approach. Faculty members, staff, and students are encouraged to integrate sustainable development and SDGs in their academic, research, and engagement activities. The latest survey showed that 2,023 out of 2,152 courses (94%) provided in the academic year of 2020 had integrated SDGs in their content and class activities. In addition, our general education program has been redesigned to serve as “Living Learning Lab (LLL)” for sustainable development projects. This revised program offers many sustainability and sustainability-related courses. They are designed to be interdisciplinary in nature. Teaching-learning activities with emphasis on “living lab” as well as experiential and project-based learning are introduced through team teaching. LLL encourages faculty members and students to work as partners for sustainable development in the surrounding communities which serve as our social living labs. During Covid-19 pandemic, we have to redesign this LLL and rethink from the learnt lessons. Nevertheless, it is our belief that these practices in the “living learning lab” will foster needed sustainability competencies leading to sustainable futures.Keyword: living learning lab, learning ecosystem, sustainable development, sustainability competencies, general education